An Introduction to Biochars and Their Uses in Agriculture - Rao Mylavarapu; Vimala Nair; Kelly Morgan (EDIS)
Biochar, also known as black carbon, is a product derived from organic materials rich in carbon and is found in soils in very stable solid forms, often as deposits. In recent years, considerable research has focused on biochar, its nature, and its properties to explore its potential benefits and negative impacts, particularly for applying to agricultural fields as amendments. This publication provides a general description of biochar, as well as technical details, benefits, and disadvantages of biochar for agricultural and environmental uses. This 4-page fact sheet was written by Rao Mylavarapu, Vimala Nair, and Kelly Morgan, and published by the UF Department of Soil and Water Science, August 2013.